Elimination profiles of betamethasone after different administration routes: Evaluation of the reporting level and washout periods to ensure safe therapeutic administrations. Issue 2 (20th October 2020) - Coll, Sergi; Monfort, Núria; Alechaga, Élida; Matabosch, Xavier; Pérez‐Mañá, Clara; Ventura, Rosa
Abstract: Betamethasone (BET) is prohibited in sports competitions when administered by systemic routes, and it is allowed by other routes for therapeutic purposes. In out‐of‐competition periods, there is no restriction of use. The present work aimed to assess the urinary excretion of BET and its metabolites after allowed and prohibited administrations to verify the suitability of the current reporting level of 30 ng/ml used to distinguish allowed and prohibited administrations and to establish washout periods for oral and intramuscular (IM) administrations when out‐of‐competition treatments are needed. BET was administered to healthy volunteers by different routes: topical (10 mg/day for 5 days, n = 6 males), intranasal (320 μg/day for 3 days, n = 4 males and 4 females), oral (0.5 mg, n = 8 males) or IM (6 mg, n = 6 males, or 12 mg, n = 4 males and 4 females). Urine and plasma samples collected before and after administration were analysed using liquid chromatography–tandem mass spectrometry. Among all studied metabolites, the parent drug was selected as the best discriminatory marker. After topical administration, BET concentrations were lower than 6.6 ng/ml. However, after intranasal treatment, some samples at concentrations close to or higher than 30 ng/ml were detected, suggesting the need to revise the current reporting level. Urinary concentrations after oral and intranasal administrations were similar, and after IM administration, concentrations were much higher. Taking into account all information, a urinary reporting level of 60 ng/ml is proposed. Washout periods of at least 48 and 96 h are recommended after oral and IM administrations, respectively. Abstract : Concentrations higher than 30 ng/ml were obtained in urine after intranasal administration. In order to avoid false AAFs, the suggestion is to increase the reporting level to 60 ng/ml, which produces a reasonable detection of prohibited administrations. Washout periods after oral and intramuscular administration need to be applied when BET is administered for therapeutic purposes in out‐of‐competition periods.